Proceedings of the International Conference on Applied Science and Technology 2019 - Social Sciences Track (iCASTSS 2019) 2019
DOI: 10.2991/icastss-19.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Explicating Human Capital Contribution for SMEs Sustainable Competitive Advantage

Abstract: Researchers debating about the role of human capital in order to increasing financial performance, sustainability and competitiveness. This study aims to examine the role of human capital in improving financial performance and competitive advantage. This study used a quantitative design through the distribution of questionnaires to managers of SMEs Wood Crafts in Badung Regency. The research sample amounted to 43 SMEs using proportional random sampling which was then analyzed with SmartPLS 3.0 software. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…SMEs can improve their human resources to become more competitive by implementing effective human resource management (Nugraha et al, 2022). Investments in employee development and training to improve the skills and knowledge of MSME players need to be made so that they can improve the performance of MSMEs (Yudistira et al, 2019). Therefore, it can be concluded that education and training play an important role in improving the performance of MSMEs.…”
Section: Human Capital Theorymentioning
confidence: 99%
“…SMEs can improve their human resources to become more competitive by implementing effective human resource management (Nugraha et al, 2022). Investments in employee development and training to improve the skills and knowledge of MSME players need to be made so that they can improve the performance of MSMEs (Yudistira et al, 2019). Therefore, it can be concluded that education and training play an important role in improving the performance of MSMEs.…”
Section: Human Capital Theorymentioning
confidence: 99%